Optimalisasi Pengelolaan Usaha di Era Digital pada CV. Nugraha Jaya Dsn. Kweden Kec. Ngasem Kab. Kediri - Ramadhan, Gema; Samimukti, Moh; Jihan, Adelia; Ningrum, Anggraini Dwi Ayu; Mubarokah, Nur Lailatul; Kintari, Fifin Widia; Rifaza, Rizkika; Najiyah, Aida Tsalitsatin (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The digital era provides great opportunities for small and medium businesses to increase efficiency and competitiveness through optimizing technology-based management. CV. Nugraha Jaya, which is located in Kweden Hamlet, Ngasem District, Kediri Regency, faces challenges in adapting to digitalization, especially in the aspects of business management, marketing and customer service. This community service activity aims to help CV. Nugraha Jaya optimizes its business management by utilizing digital technology, such as stock management applications, e-commerce platforms and social media marketing. A Participatory Action Research (PAR) approach was used in this activity, which involved needs analysis, intensive training, and technical assistance. The results of the activity showed an increase in the understanding and skills of the CV team. Nugraha Jaya in using digital technology to increase operational efficiency and expand market reach. Overall, this activity succeeded in having a positive impact on more modern, efficient and competitive business management in the digital era.